(untitled) (International Journal of Food and Nutritional Sciences, 2025)
Background : Chhattisgarh has a rich culture of consumption of a wide variety of vegetables, specially green leafy vegetables. However, a large number of the women of Chhattisgarh still are anemic. Purpose: The study aimed to evaluate the dietary diversity of women of Chhattisgarh and to compare the data with that recommended by FAO in Minimum Dietary Diversity for Women. Method: The data was collected from women of Chhattisgarh through an online questionnaire form. 100 samples were targeted, 103 forms were collected. The data was analyzed on google sheets and compared with the information from NFHS-5. Result: The average overall dietary diversity score of Chhattisgarhi women came up to be about 8 which is very good. Consumption of green leafy vegetables by women in Chhattisgarh has reduced minimally (by 5.1%) when compared with data collected in 2021 (NFHS-5), but is still above average than that was consumed by population of India (90.63%). Conclusion: Dietary diversity of women in Chhattisgarh was good, however, the data does not match with the health conditions. Therefore improvement in diets should be made to improve nutrient absorption.